Air Quality and Public Perception of Environmental Pollution Around the Factory Area - Ayu Novitrie; Jihad Wafiqa Rahmah; Siti Septiani Rulyah (CV. Get Press Indonesia, 2025)
Industrial activities around the Lubuk Begalung rubber factory in Padang City pose risks to air quality, raising community concerns about health and comfort. This study aimed to evaluate air quality and analyze local perceptions of pollution caused by factory operations. A quantitative survey with purposive sampling was conducted among 75 residents living within a 2 km radius of the factory for at least two years. Data were collected through questionnaires and analyzed descriptively using frequency, percentage, mean, and standard deviation. Relationships between perceived air quality and pollution impacts were examined using Spearman or Pearson correlation. Findings revealed that 60% of respondents frequently detected strong odors during production hours, while 55% reported mild respiratory problems, including coughing and throat irritation. Statistical analysis indicated a significant correlation between odor intensity and health complaints (rs = 0.62; p < 0.01). In addition, 70% of respondents felt a decline in environmental comfort, which was also significantly related to health complaints (rs = 0.58; p < 0.01). These results confirm that factory emissions negatively affect both physical and psychological well-being of nearby residents. The study emphasizes the need for stricter emission monitoring, adoption of environmentally friendly technologies, and stronger community involvement in environmental surveillance. Collaboration among industry, government, and local communities is essential to maintain air quality and minimize long-term health impacts.